ECONOMIC ANALYSIS OF THE USE OF MATA LELE (Lemna minor) MEAL FOR BROILER RATIONS - S F Jamis; N Irwani; R Noviadi (Politeknik Negeri Lampung, 2022)
High price of commercial feed causes the level of profits to be low and even does not rule out the possibility that farmers will also suffer losses. Alternative feed ingredients that can replace some of the commercial feeds that can be used are Lemna minor. This research was conducted in State Polythecnic of Lampung broiler cage. The aim of this research to analyzing economics utilization of mata lele (Lemna minor) flour for broiler rations. This research used two treatments, P0= rations without mata lele flour and P1= rations with 4,5% additional mata lele flour. The data obtained are calculated with Microsoft excel and analyzed descriptively. The result of research rations with mata lele flour can reduce the total cost of production and has an economical value. generates BEP Price 21.096,52; BEP Product 74,85 Kg.; IOFC Rp. 2.058.106,02.; R/C 1,42; B/C 0,42.